Desigualdad en las trayectorias educativas de jóvenes migrantes: Disquisiciones preliminares - Gonzalez, Mariana Alejandra (Universidad de Costa Rica, 2022)
The education is a human right; warranted in Argentina by the Education National Law (26.206, 2006) and the Migration National Law (25.871, 2003), among others regulations. In which it is expressed the mandatory of the secondary school for all the habitants in Argentina´s territory, in conditions of equality, without any discrimination. However, it happens that this right is violated for young migrants. The aim of this essay is to analyze the inequality in educational trajectories of young migrants students, in the Metropolitan Area of Buenos Aires. In order to that, it is presented an historical tale about origins of the secondary school and its consolidation, the way migrants students are integrated, from their experiences and relations with pairs and teachers, to their performances, and its contextualization in the familiar project. Finally, it is presented the Sociology of Experience, as an epistemological tool, that allows the comprehensive approach to this problem. This essay concludes that the school is in a privileged position for the design of strategies that can counteract the several factors which condition a scholar trajectory, in order to design more equality practices.